Arthrocentesis for temporomandibular joint disorders: a network meta-analysis of randomised controlled trials - Jun-Ming Zhang; Jie Yun; Tian-Qi Zhou; Ying Zhang; Chao Gao (BMC, 2024)
Abstract Objective Clinical studies have demonstrated the effectiveness of arthrocentesis in managing temporomandibular joint disorders (TMDs). However, there is a lack of consensus among these studies regarding the selection of injectables. Furthermore, an increasing number of drugs have been tested for TMDs in recent years, complicating the decision-making process for clinicians. This study conducted a network meta-analysis of randomized controlled trials (RCTs) to compare the clinical efficacy of different arthrocentesis treatment regimens. Methods We conducted a comprehensive search of Embase, PubMed, Cochrane Library, and Web of Science to gather articles on RCTs pertaining to the management of TMDs using arthrocentesis. This search spanned from inception of these databases up to July 29, 2024. We then performed a network meta-analysis using Stata 17.0 software. The outcome indicators used were VAS scores and changes in unassisted maximum opening. To determine the efficacy of each regimen, we employed surface-under the cumulative ranking curve (SUCRA) ranking. Result Forty RCTs were included, encompassing 1904 temporomandibular joints (TMJs) cases. Treatment options encompass platelet-rich plasma (PRP), hyaluronic acid (HA), corticosteroids (CS), bone marrow concentrate (BMAC), injectable platelet-rich fibrin (i-PRF), concentrated growth factor (CGF), Tenoxicam (TX), microfragmented adipose tissue (FAT), and their combination regimens. The SUCRA ranking revealed that the most effective treatment options at 1-, 3-, and 6-months post-arthrocentesis were HA + PRP, i-PRF, and BMAC, respectively. Conclusion HA + PRP, i-PRF and BMAC may represent the optimal arthrocentesis agents for the management of TMDs symptoms and restoration of TMJ function in the short, medium, and long term, respectively. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/ , identifier CRD42024563975.